2005
DOI: 10.1007/s11167-005-0354-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pore Structure of Monolithic Polymeric Sorbents

Abstract: The pore structure of monolithic sorbents prepared by photoinduced copolymerization of 2,3-epoxypropyl methacrylate with ethylene glycol dimethacrylate was studied. The parameters of the pore structure of these copolymers were examined as influenced by the quantitative ratio of pore-forming agents and the type and concentration of the initiators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The main factors affecting photopolymerization are the light intensity, as well as nature and concentration of the initiator. Khimich et al [67] investigated the preparation of poly(GMA-co-EDMA) monoliths using photoinitiated polymerization with (Darokur-1173) as initiator and cyclohexanol as a porogen. The use of 1 wt% of this initiator provided a 96% yield after 20 min of irradiation with UV light having a wavelength of 320 nm.…”
Section: Photopolymerizationmentioning
confidence: 99%
“…The main factors affecting photopolymerization are the light intensity, as well as nature and concentration of the initiator. Khimich et al [67] investigated the preparation of poly(GMA-co-EDMA) monoliths using photoinitiated polymerization with (Darokur-1173) as initiator and cyclohexanol as a porogen. The use of 1 wt% of this initiator provided a 96% yield after 20 min of irradiation with UV light having a wavelength of 320 nm.…”
Section: Photopolymerizationmentioning
confidence: 99%
“…As mentioned previously, the presence of a foreign solvent (1,4‐dioxane) in the polymerization mixture leads to significant changes in the process of macroporous structure formation. Earlier, in the case of the synthesis of poly(GMA‐ co ‐EDMA) monoliths by photoinitiated free‐radical polymerization, we demonstrated that the use of CyOH as the only porogen was absolutely sufficient to obtain a material with an average pore size of about 900–1000 nm 28. In contrast, in the case of the preparation of poly(HPIEAA‐ co ‐GMA‐ co ‐EDMA), the use of CyOH as the only porogen led to the formation of a monolith with an average pore size of 30 nm (sample M1).…”
Section: Resultsmentioning
confidence: 95%
“…Earlier, in the case of the synthesis of poly(GMA-co-EDMA) monoliths by photoinitiated free-radical polymerization, we demonstrated that the use of CyOH as the only porogen was absolutely sufficient to obtain a material with an average pore size of about 900-1000 nm. 28 In contrast, in the case of the preparation of poly(HPIEAA-co-GMA-co-EDMA), the use of CyOH as the only porogen led to the formation of a monolith with an average pore size of 30 nm (sample M1). Besides that, SEM data showed that the surface of this monolithic material had numerous defects [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that structure formation of the monolithic polymer, par ticularly, AMA-EDMA copolymer, depends substantial ly on the nature and ratio of thermodynamically "bad" solvents (porogens) in the organic phase. 7, 8 The high affin ity of the porogens to alkyl methacrylates in the composition of monoliths OMA-EDMA 5 and LMA-EDMA 6 is like ly to transform the "bad" porogens into "good" solvents and thus decreases sharply the fraction of macropores in the monolith structure. Thus, at this stage of the work we conclude that the further elongation of the alkyl radical in the alkyl methacrylate molecule with retention of the de scribed procedure of synthesis has no prospects.…”
Section: Resultsmentioning
confidence: 99%